Effects of interleukin‐10 on cutaneous wounds and scars in humans of African continental ancestral origin. Issue 3 (May 2014) - Kieran, Ingrid; Taylor, Catherine; Bush, Jim; Rance, Mark; So, Karen; Boanas, Adam; Metcalfe, Anthony; Hobson, Rosalind; Goldspink, Nick; Hutchison, John; Ferguson, Mark
Abstract Scars in humans of African continental ancestry heal with an exaggerated inflammatory response and a generally wider scar. Interleukin‐10 is an anti‐inflammatory and antifibrotic cytokine. A randomized controlled trial in Caucasians found that exogenous interleukin‐10 resulted in improved macroscopic scar appearance and reduced scar redness. We investigated the effects of interleukin‐10 on cutaneous scarring in volunteers of African ancestral origin in an exploratory, single‐center, within‐subject, double‐blind randomized controlled trial. Fifty‐six subjects received two of four potential prerandomized concentrations of interleukin‐10 (5, 25, 100, and 250 ng/100 µL) in two full‐thickness incisions on the upper inner arms. Anatomically matching incisions on the contralateral arm were treated with placebo. Scars were excised at 1 month for histological analysis and were redosed with the same regimen. Resultant excision scars were followed up for 12 months for scar width measurement and scoring. Scoring was performed by trial doctors, subjects, and a panel. Incisions treated with 100 ng/100 µL interleukin‐10 had significantly reduced microscopic scar widths. Incisions treated with 5 and 25 ng/100 µL interleukin‐10 were also narrower, but not significantly. There were no differences observed in pro‐inflammatory or pro‐fibrotic markers between interleukin‐10 and placebo treatment. There was no long‐term evidence that 100 ng/100 µL interleukin‐10 had a therapeutic effect on macroscopic scar width or appearance, as excisions treated with this concentration were significantly wider than placebo between 8 and 12 months of maturation. Doctors showed a trend toward favoring the macroscopic appearance of placebo‐treated excisions compared with those treated with 250 ng/100 µL interleukin‐10. Panelists scored placebo‐treated excisions as significantly better‐appearing than those treated with 250 ng/100 µL interleukin‐10. Doctors' scores showed a trend toward favoring treatment with 5 ng/100 µL interleukin‐10 at 10 and 11 months post‐excision. Subjects showed a trend toward favoring treatment with 5 ng/100 µL interleukin‐10 between 5 and 9 months postexcision. Analysis of images of markedly improved scars revealed a potential subset of responders among those treated with 5 ng/100 µL interleukin‐10. No concentration of interleukin‐10 produced a statistically significant improvement in scarring compared with placebo.